Nitrogen in bio-oil produced from hydrothermal liquefaction of biomass: A review - Leng, Lijian; Zhang, Weijin; Peng, Haoyi; Li, Hailong; Jiang, Shaojian; Huang, Huajun (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
[Display omitted] •20–40% of the N in biomass feedstock would distribute into bio-oil during the HTL.•Effects of biomass and HTL processing parameters on bio-oil N were overviewed.•Pretreatment and co-HTL of biomass are effective to mediate bio-oil N.•High bio-oil yield is accompanied by high bio-oil N content.•Bio-oil extraction solvent & procedure are decisive to bio-oil N. Hydrothermal liquefaction (HTL) of biomass, especially that of high moisture such as microalgae, macroalgae, sludge, manure, and food waste, for the production of bio-oil has been widely concerned worldwide. However, the contents of nitrogen (N) in these biomasses are commonly high, and 20–40% of the N in the raw biomasses would distribute into bio-oil during the HTL process, resulting in a high content of N in bio-oil, sometimes up to 10 wt%. The combustion of N-rich bio-oil will probably induce massive emission of nitrogen oxides. The transformation behavior of N has not yet been fully understood, and the denitrogenation is a critical issue during bio-oil production and upgrading. This review comprehensively summarized the effects of the type, composition, and pretreatment of biomass and HTL processing parameters, such as temperature, residence time, solid loading, reaction solvent, extraction solvent/procedure, and catalyst, on the N content of bio-oil. The N conversion mechanisms in the HTL process were also clarified. Research gaps were identified, and future research directions were finally proposed to achieve the production of bio-oil with low N content.